Method for manufacturing new building material by using household garbage fly ash

CN122977758APending Publication Date: 2026-10-27ZHEJIANG WEIHANG NEW MATERIAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411500737.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-24
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0005]针对现有技术的不足,本发明提供了一种利用生活垃圾发电飞灰制造新型建材的方法,解决了现有技术在利用垃圾焚烧飞灰制备建材的过程中,仍然存在重金属稳定化效果不理想、材料力学性能不足、环境安全性有待提高的问题

Benefits of technology

[0030]1、本发明通过将生活垃圾焚烧发电产生的飞灰经过重金属稳定化处理后,成功应用于新型建材的生产,实现了对飞灰的资源化利用。通过将原本有害的废弃物转化为有用的建筑材料,不仅减少了飞灰的填埋量,降低了对土壤和地下水的污染风险,还节约了填埋场地资源,符合环境保护和可持续发展的要求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122977758A_ABST
    Figure CN122977758A_ABST
Patent Text Reader

Abstract

This application relates to the field of building material preparation and discloses a method for manufacturing new building materials using fly ash from municipal solid waste incineration power generation. The method includes the following steps: Step (1) Fly ash treatment: The fly ash generated from municipal solid waste incineration power generation undergoes heavy metal stabilization treatment to reduce the leaching toxicity of heavy metals; Step (2) Preparation or selection of photocatalyst: Materials with photocatalytic properties are prepared or selected; Step (3) Preparation of mixture: The stabilized fly ash, cementitious materials, photocatalyst, aggregate, and water are mixed to form a mixture with good workability; Step (4) Molding and curing: The mixture is poured into a mold and compacted by vibration. By successfully applying the fly ash generated from municipal solid waste incineration power generation to the production of new building materials after heavy metal stabilization treatment, the resource utilization of fly ash is realized. This reduces the risk of pollution to soil and groundwater, meeting the requirements of environmental protection and sustainable development.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of building material preparation technology, specifically a method for manufacturing new building materials using fly ash from municipal solid waste power generation. Background Technology

[0002] With rapid urbanization and industrialization, the amount of municipal solid waste generated is increasing year by year. Waste-to-energy incineration, as an effective waste treatment method, features waste reduction, resource recovery, and harmlessness, achieving the dual goals of waste treatment and energy recovery. However, the incineration process produces a large amount of fly ash, which contains harmful substances such as heavy metals and dioxins, posing a potential threat to the environment and human health. How to safely and effectively treat and utilize waste incineration fly ash has become a research hotspot in the fields of environmental protection and resource utilization.

[0003] Currently, the main methods for treating fly ash from waste incineration include stabilization / solidification followed by landfilling and resource utilization. Stabilization / solidification typically uses cement, lime, and other cementing materials to fix the heavy metals in the fly ash within a solid matrix, followed by secure landfilling. Regarding resource utilization, some studies have explored using fly ash to produce building materials such as cement, concrete, and ceramics, aiming to achieve both resource recovery and volume reduction. These methods, to some extent, reduce the environmental impact of fly ash and enable the recycling of some resources.

[0004] However, existing technologies for preparing building materials from waste incineration fly ash still face challenges such as unsatisfactory heavy metal stabilization, insufficient material mechanical properties, and room for improvement in environmental safety. In particular, the risk of heavy metal leaching from fly ash limits its large-scale application in building materials. Summary of the Invention

[0005] To address the shortcomings of existing technologies, this invention provides a method for manufacturing new building materials using fly ash from municipal solid waste power generation. This method solves the problems of unsatisfactory heavy metal stabilization, insufficient mechanical properties of materials, and the need to improve environmental safety that still exist in the process of preparing building materials using fly ash from waste incineration.

[0006] To achieve the above objectives, the present invention provides the following technical solution: a method for manufacturing new building materials using fly ash from municipal solid waste power generation, comprising the following steps:

[0007] Step (1), Fly ash treatment: The fly ash generated from municipal solid waste incineration power generation is subjected to heavy metal stabilization treatment to reduce the leaching toxicity of heavy metals.

[0008] Step (2), Preparation or selection of photocatalyst: Prepare or select materials with photocatalytic properties;

[0009] Step (3), Preparation of mixture: Mix the stabilized fly ash, cementitious material, photocatalyst, aggregate and water to form a mixture with good workability;

[0010] Step (4), molding and curing: Pour the mixture into the mold, vibrate and compact it to form building material products; cure the molded products until they meet the specified performance requirements.

[0011] Preferably, in step (1), the heavy metal stabilization treatment includes: mixing fly ash with diammonium hydrogen phosphate and ferrous sulfate heptahydrate, wherein the mass ratio of diammonium hydrogen phosphate to fly ash is m1:m FA =1:10, the mass ratio of ferrous sulfate heptahydrate to fly ash is m2:m FA =1:10; During the mixing process, add at a rate of 1 minute Calcium hydroxide was gradually added at a constant rate until the pH of the solution reached 10 ± 0.5; heavy metal ions Pb 2+ Cd 2+ Cr 3+ It reacts with phosphate and hydroxide ions to form insoluble phosphates and hydroxides. The reaction equation is as follows:

[0012]

[0013] M n+ +nOH - →M(OH) n ↓

[0014] Among them, M n+ These are heavy metal ions.

[0015] Preferably, in step (2), the photocatalyst is nitrogen-doped nano-titanium dioxide, and its preparation method includes: using tetrabutyl titanate as a precursor, dissolving it in anhydrous ethanol at a volume ratio of... Precursor solution A is formed; deionized water and glacial acetic acid are mixed at a volume ratio of... Solution B was formed, and the pH was adjusted to 3-4. Under ice bath conditions, solution A was slowly added to solution B at a dropping rate of u = 1 mL / min, and stirred for 2 hours to obtain a homogeneous sol. Urea was added to the sol at a molar ratio of n(CO(NH2)2):n(Ti(OC4H9)4) = 1:1. After drying the gel, it was calcined at 500℃ under a nitrogen atmosphere at a heating rate of 5℃ / min for 3 hours, with a nitrogen flow rate of Q = 200 mL / min, to obtain nitrogen-doped nano-TiO2.

[0016] Preferably, in step (2), the nitrogen doping mechanism is as follows: urea decomposes at high temperature to produce ammonia (NH3). Nitrogen atoms in the ammonia replace oxygen atoms in the TiO2 lattice, forming TiO2. 2-x N x The reduction in band gap energy is due to the formula Description, in which ΔE represents the band gap energy of pure TiO2, while ΔE represents the reduction in band gap energy caused by doping, which enhances the response to visible light.

[0017] Preferably, in step (3), the mixing ratio of the mixture is as follows: stabilized fly ash: 30% of the total mass of cementitious materials; cement: 65%; nitrogen-doped nano-TiO2: 5%; water-cement ratio = 0.35; water-reducing agent added, accounting for 1% of the total mass of cementitious materials.

[0018] Preferably, in step (3), to prevent the agglomeration of nano-TiO2, nitrogen-doped nano-TiO2 is dispersed in a water-reducing agent solution by ultrasonic dispersion. The ultrasonic frequency is f = 20 kHz and the time is 30 minutes to form a stable nano suspension. The nano suspension is added to a mixer along with other raw materials. The stirring speed is 500 rpm and the stirring time is 10 minutes to ensure the uniformity of the mixture.

[0019] Preferably, in step (4), the molding method is vacuum vibration molding: the mold is placed in a vacuum environment with a vacuum degree of P = -0.08MPa; the mold is vibrated at a vibration frequency of 50Hz for 2 minutes to improve the density and surface quality of the specimen.

[0020] Preferably, in step (4), during the curing process, steam curing is carried out after the initial curing: heating stage: heating up to 80°C at a heating rate of 10°C / h; constant temperature stage: keeping warm at 80°C for 8 hours; cooling stage: cooling down to room temperature at a cooling rate of 10°C / h; steam curing accelerates the hydration reaction of cement and fly ash and improves the early strength of the material.

[0021] Preferably, in step (4), the novel building material obtained has photocatalytic properties, and the testing method includes: immersing a specimen with dimensions of 50mm×50mm×10mm into a methylene blue solution with an initial concentration of C0=10mg / L and V=200mg / L; irradiating it with a 300W xenon lamp with a light intensity of I=100mW / cm². 2 The distance between the samples is 10 cm; samples are taken every 30 minutes, and the absorbance A of the solution is measured. t Calculate the degradation rate η;

[0022]

[0023] Where A0 is the initial absorbance;

[0024] Within 3 hours, the degradation rate η is not less than 80%.

[0025] Preferably, in step (4), the mechanical property testing of the obtained new building material includes: testing the compressive strength of the cubic specimen using a pressure testing machine; the loading speed is v = 0.5 MPa / s; and the compressive strength f c The calculation formula is:

[0026]

[0027] Where F is the failure load and A is the compression area (100mm×100mm);

[0028] Compressive strength f at 28 days of age c Not less than 50MPa.

[0029] This invention provides a method for manufacturing new building materials using fly ash from municipal solid waste power generation. It has the following beneficial effects:

[0030] 1. This invention successfully utilizes fly ash generated from municipal solid waste incineration power generation by stabilizing it with heavy metals in the production of new building materials, thus realizing the resource utilization of fly ash. By transforming this originally harmful waste into useful building materials, it not only reduces the amount of fly ash going to landfills and lowers the risk of soil and groundwater pollution, but also saves landfill resources, meeting the requirements of environmental protection and sustainable development.

[0031] 2. This invention stabilizes heavy metal ions in fly ash by adding chemical reagents such as diammonium hydrogen phosphate and ferrous sulfate, generating insoluble phosphates and hydroxides, thus fixing the heavy metals in a stable form within the building materials. Heavy metal leaching tests show that the leaching concentration of heavy metal ions in the building materials is below the national standard limit, significantly reducing the potential harm of heavy metals to the environment and human health, and improving the environmental safety of the building materials.

[0032] 3. In the preparation process of the building materials, this invention rationally designs the mixing ratio of fly ash, cement, and photocatalyst, and employs technologies such as ultrasonic dispersion and vacuum vibration molding to ensure the uniformity and density of the materials. Test results show that the prepared building materials achieve a compressive strength of 52 MPa, meeting the mechanical performance requirements of building materials. The high strength and durability of the materials ensure their safety and reliability in engineering applications.

[0033] 4. This invention achieves waste reduction, resource recovery, and harmless treatment, aligning with the development concept of a circular economy. By transforming industrial waste into high-value-added products, it promotes resource recycling and reduces environmental impact. The promotion of this technology helps enhance public awareness of environmental protection, drives the development of green building and the environmental protection industry, and has significant social benefits. Attached Figure Description

[0034] Figure 1 This is a flowchart of the method of the present invention. Detailed Implementation

[0035] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0036] Example 1:

[0037] Please see the appendix Figure 1 This invention provides a method for manufacturing new building materials using fly ash from municipal solid waste power generation, comprising the following steps:

[0038] Step (1), Fly ash treatment: The fly ash generated from municipal solid waste incineration power generation is subjected to heavy metal stabilization treatment to reduce the leaching toxicity of heavy metals.

[0039] Step (2), Preparation or selection of photocatalyst: Prepare or select materials with photocatalytic properties;

[0040] Step (3), Preparation of mixture: Mix the stabilized fly ash, cementitious material, photocatalyst, aggregate and water to form a mixture with good workability;

[0041] Step (4), molding and curing: Pour the mixture into the mold, vibrate and compact it to form building material products; cure the molded products until they meet the specified performance requirements.

[0042] In step (1), the heavy metal stabilization treatment includes: mixing fly ash with diammonium hydrogen phosphate and ferrous sulfate heptahydrate, wherein the mass ratio of diammonium hydrogen phosphate to fly ash is m1:m FA =1:10, the mass ratio of ferrous sulfate heptahydrate to fly ash is m2:m FA =1:10; During the mixing process, add at a rate of 1 minute Calcium hydroxide was gradually added at a constant rate until the pH of the solution reached 10 ± 0.5; heavy metal ions Pb2+ Cd 2+ Cr 3+ It reacts with phosphate and hydroxide ions to form insoluble phosphates and hydroxides. The reaction equation is as follows:

[0043]

[0044] M n+ +nOH - →M(OH) n ↓

[0045] Among them, M n+ These are heavy metal ions.

[0046] In step (2), the photocatalyst is nitrogen-doped nano-titanium dioxide, which is prepared by dissolving tetrabutyl titanate as a precursor in anhydrous ethanol at a volume ratio of... Precursor solution A is formed; deionized water and glacial acetic acid are mixed at a volume ratio of... Solution B was formed, and the pH was adjusted to 3-4. Under ice bath conditions, solution A was slowly added to solution B at a dropping rate of u = 1 mL / min, and stirred for 2 hours to obtain a homogeneous sol. Urea was added to the sol at a molar ratio of n(CO(NH2)2):n(Ti(OC4H9)4) = 1:1. After drying the gel, it was heated to 500℃ at a heating rate of 5℃ / min under a nitrogen atmosphere, held at that temperature for 3 hours, and the nitrogen flow rate was Q = 200 mL / min to complete the calcination, thus obtaining nitrogen-doped nano-TiO2.

[0047] In step (2), the nitrogen doping mechanism is as follows: urea decomposes at high temperature to produce ammonia (NH3). Nitrogen atoms in the ammonia replace oxygen atoms in the TiO2 lattice, forming TiO2. 2-x N x The reduction in band gap energy is due to the formula Description, in which ΔE represents the band gap energy of pure TiO2, while ΔE represents the reduction in band gap energy caused by doping, which enhances the response to visible light.

[0048] In step (3), the mix proportions are as follows: stabilized fly ash: 30% of the total mass of cementitious materials; cement: 65%; nitrogen-doped nano-TiO2: 5%; water-cement ratio = 0.35; water-reducing agent is added, accounting for 1% of the total mass of cementitious materials.

[0049] In step (3), to prevent the agglomeration of nano-TiO2, nitrogen-doped nano-TiO2 is dispersed in the water-reducing agent solution by ultrasonic dispersion method. The ultrasonic frequency is f = 20 kHz and the time is 30 minutes to form a stable nano suspension. The nano suspension is added to the mixer along with other raw materials. The stirring speed is 500 rpm and the stirring time is 10 minutes to ensure the uniformity of the mixture.

[0050] In step (4), the molding method is vacuum vibration molding: the mold is placed in a vacuum environment with a vacuum degree of P = -0.08MPa; the mold is vibrated at a frequency of 50Hz for 2 minutes to improve the density and surface quality of the specimen.

[0051] In step (4), during the curing process, steam curing is carried out after the initial curing: heating stage: heating up to 80℃ at a heating rate of 10℃ / h; constant temperature stage: keeping at 80℃ for 8 hours; cooling stage: cooling down to room temperature at a cooling rate of 10℃ / h; steam curing accelerates the hydration reaction of cement and fly ash and improves the early strength of the material.

[0052] In step (4), the obtained new building material has photocatalytic properties, and the testing method includes: immersing a specimen with dimensions of 50mm×50mm×10mm into a methylene blue solution with an initial concentration of C0=10mg / L and V=200mg / L; irradiating it with a 300W xenon lamp with a light intensity of I=100mW / cm². 2 The distance between the samples is 10 cm; samples are taken every 30 minutes, and the absorbance A of the solution is measured. t Calculate the degradation rate η;

[0053]

[0054] Where A0 is the initial absorbance;

[0055] Within 3 hours, the degradation rate η is not less than 80%.

[0056] In step (4), the mechanical property tests of the obtained new building material include: using a pressure testing machine to test the compressive strength of the cubic specimen; the loading speed is v = 0.5 MPa / s; the compressive strength f c The calculation formula is:

[0057]

[0058] Where F is the failure load and A is the compression area (100mm×100mm);

[0059] Compressive strength f at 28 days of age c Not less than 50MPa.

[0060] In one embodiment, step one: heavy metal stabilization treatment of fly ash

[0061] 1.1 Collection and Pretreatment of Fly Ash

[0062] In this embodiment, fly ash is first collected from the flue gas treatment system (such as a bag filter) of a municipal solid waste incineration power plant, and is designated as FA0. To ensure the uniformity and representativeness of the fly ash, fly ash from different time periods should be collected and mixed during the collection process.

[0063] Next, the collected fly ash is dried. The specific method is as follows: FAO is evenly spread on a stainless steel tray, with a thickness not exceeding 20mm to prevent uneven drying. The tray is placed in a forced-air drying oven, and the temperature is set to T1 = 105℃ for a drying time of t1 = 24 hours. The purpose of this step is to remove free water from the fly ash, preventing moisture from affecting the reaction effect during subsequent processing. After drying, the fly ash FA1 is ground and sieved. Specifically, FA1 is placed in a ball mill and ground for t2 = 2 hours at a speed n1 = 60 rpm. The ground fly ash is then sieved through a 75μm (200 mesh) standard sieve, and the fine powder passing through the sieve is collected to obtain fine fly ash FA2 with uniform particle size. This step aims to increase the specific surface area of ​​the fly ash, which is beneficial for the full conduct of subsequent chemical reactions. Through the above pretreatment, the physical properties of the fly ash are unified, laying the foundation for subsequent heavy metal stabilization treatment.

[0064] 1.2 Chemical stabilization treatment

[0065] In this embodiment, a combined stabilization method using phosphate and ferrous sulfate is employed to effectively fix heavy metals in fly ash.

[0066] First, prepare the stabilizer solution:

[0067] Diammonium hydrogen phosphate solution (S1): Weigh m1 = 50g of diammonium hydrogen phosphate and dissolve it in V1 = 500ml of deionized water. Stir until completely dissolved to obtain a solution with a concentration of C1 = 0.5mol / L. Next, place FA2 into an acid- and alkali-resistant stirred reactor and add S1 and S2 solutions sequentially according to a solid-liquid ratio (mass ratio) of 1:1. Start stirring at a speed of u1 = 300rpm for a stirring time of t3 = 2 hours. During stirring, calcium hydroxide is gradually added to adjust the pH of the solution. The specific addition method is: at a rate of Δ... m =0.1m FA Add calcium hydroxide evenly and continuously, monitoring the pH of the solution in real time, until the pH reaches 10 ± 0.5. Controlling the pH is crucial in this step because an alkaline environment promotes the precipitation and fixation of heavy metals.

[0068] Under the above conditions, the heavy metal ions Pb in fly ash2+ Cd 2+ Cr 3+ It reacts with phosphate and hydroxide ions to form insoluble phosphates and hydroxides. The reaction equation is as follows:

[0069]

[0070] M n+ +nOH - →M(OH) n ↓

[0071] Among them, M n+ These are heavy metal ions.

[0072] In addition, ferrous sulfate will generate ferric hydroxide Fe(OH)2 and Fe(OH)3 under alkaline conditions. These hydroxides have good adsorption properties and can further adsorb heavy metal ions, thus enhancing the stabilization effect.

[0073] After the reaction is complete, the mixture is subjected to solid-liquid separation. Specifically, the mixture is filtered using a vacuum filtration device, and the solid portion FA3 is collected. To remove residual soluble salts, FA3 is washed with deionized water until the conductivity of the filtrate is close to that of deionized water. Then, FA3 is placed in a drying oven at a temperature of T2 = 105℃ for a drying time of t4 = 12 hours, yielding stabilized fly ash FA4. Through the above chemical stabilization treatment, the heavy metals in the fly ash are fixed into insoluble compounds, reducing the risk of leaching into the environment and ensuring the safe application of fly ash in building materials.

[0074] 1.3 Stabilization effect

[0075] In this embodiment, the stabilization effect was verified by conducting heavy metal leaching tests on fly ash before and after stabilization treatment using the acetic acid buffer solution method. The results showed that the leaching concentrations of heavy metal ions in the stabilized fly ash (FA4) were all below the national standard limits, meeting environmental protection requirements.

[0076] Step 2: Preparation of nitrogen-doped nano-titanium dioxide photocatalyst

[0077] 2.1 Preparation of nano-TiO2 by sol-gel method

[0078] In this embodiment, nano-titanium dioxide was prepared using the sol-gel method, and its photocatalytic performance was enhanced by nitrogen doping modification. First, precursor solution A was prepared: tetrabutyl titanate was added at a volume ratio of... Dissolve in anhydrous ethanol and stir well to obtain a transparent precursor solution A. Simultaneously, prepare hydrolysis solution B: mix deionized water and glacial acetic acid in a volume ratio of... Stir thoroughly and adjust the pH of the solution to 3-4. The addition of glacial acetic acid helps control the rate of the hydrolysis reaction and prevents the formation of excessively large TiO2 particles. Next, under ice bath conditions, solution A is slowly added dropwise to solution B at a rate of u = 1 mL / min, while continuously stirring for t5 = 2 hours, resulting in a uniform and transparent sol. The purpose of the ice bath is to lower the reaction temperature, further control the rate of the hydrolysis reaction, and obtain nanoparticles with smaller particle sizes.

[0079] 2.2 Nitrogen Doping Modification

[0080] In this embodiment, to enable TiO2 to exhibit photocatalytic activity under visible light, urea is added to the sol for nitrogen doping. Specifically, the amount of urea to be added is calculated according to a molar ratio of n(CO(NH2)2):n(Ti(OC4H9)4) = 1:1. The urea is dissolved in the sol, and stirring is continued for t6 = 1 hour to ensure that the urea is uniformly distributed in the sol.

[0081] 2.3 Gel drying and calcination

[0082] The sol was left to stand at room temperature for t7 = 24 hours to allow it to gradually form a gel. The gel was then dried in a drying oven at T3 = 80℃ for t8 = 12 hours to obtain a dried gel powder. Next, the dried gel powder was placed in a tube furnace and high-purity nitrogen gas was introduced at a flow rate Q = 200 mL / min to prevent oxygen from the air from participating in the reaction. The temperature was increased to T4 = 80℃ at a rate R = 5℃ / min and held for t9 = 3 hours to complete the calcination, yielding nitrogen-doped nano-titanium dioxide (TiO₂). 2-x N x .

[0083] During the calcination process, urea decomposes at high temperatures to produce ammonia and carbon dioxide.

[0084]

[0085] HNCO + H₂O → NH₃ + CO₂

[0086] Nitrogen atoms from the generated ammonia gas enter the TiO2 lattice at high temperature, replacing some oxygen atoms and forming nitrogen-doped TiO2. 2-x N x Nitrogen doping reduces the band gap energy of TiO2 from Reduced to E g The voltage is approximately 2.5 eV, which enhances the absorption capacity of TiO2 for visible light and improves its photocatalytic performance.

[0087] Example 2:

[0088] Adding slag powder to enhance the mechanical properties of building materials

[0089] I. Implementation Overview

[0090] In this preferred embodiment, in order to further improve the mechanical properties and durability of the building materials, in addition to the original stabilized fly ash, cement and nitrogen-doped nano-TiO2, slag powder is added. Slag powder has high activity and can undergo secondary hydration reaction with cement hydration products to generate more gel products, fill the pores and improve the density and strength of the material.

[0091] II. Specific Implementation Steps

[0092] Step 1: Raw material preparation

[0093] In this embodiment, the proportions of the raw materials have been adjusted, as follows:

[0094] Stabilized fly ash FA4: accounts for 20% of the total mass of cementitious materials.

[0095] Cement (PO 42.5): accounts for 50% of the total mass of cementitious materials.

[0096] Grinded slag powder (GGBFS): accounts for 25% of the total mass of cementitious materials.

[0097] Nitrogen-doped nano-TiO2: accounts for 5% of the total mass of the cementitious material.

[0098] Water-to-binder ratio: W / B = 0.30.

[0099] Water-reducing agent (polycarboxylate): 1% of the total mass of cementitious materials.

[0100] Aggregates: fine aggregate (sand) and coarse aggregate (crushed stone), designed according to conventional concrete mix proportions.

[0101] Step 2: Preparation of the mixture

[0102] 2.1 nanometer TiO2 dispersion.

[0103] Similar to the aforementioned specific implementation method, nitrogen-doped nano-TiO2 was added to the water-reducing agent solution, and an ultrasonic disperser was used at a frequency of f = 20 kHz and a time of t = 30 minutes to form a stable nano-suspension.

[0104] 2.2 Hybrid Process

[0105] Step 1: Mixing dry ingredients

[0106] Weigh the stabilized fly ash FA4 cement and slag powder according to the proportion, add them to the mixer, dry mix for t=5 minutes, and mix at a speed of u=200rpm.

[0107] Step 2: Add aggregate

[0108] Add fine and coarse aggregates and continue dry mixing for t = 2 minutes.

[0109] Step 3: Mixing wet materials

[0110] Gradually add the nano suspension and the remaining water, increase the stirring speed to u=500rpm, wet mix for t=10 minutes, until the mixture is uniform.

[0111] Step 3: Shaping and Curing

[0112] Similar to the aforementioned specific implementation method, vacuum vibration molding technology and steam curing method are used.

[0113] Step 4: Performance Testing

[0114] 4.1 Mechanical property testing

[0115] compressive strength

[0116] 7-day compressive strength f c It reaches 45 MPa.

[0117] 28-day compressive strength f c It reaches 60 MPa.

[0118] 4.2 Durability Test

[0119] Resistance to chloride ion penetration

[0120] A rapid chloride ion penetration test (RCPT) was conducted according to ASTM C1202 standard. The test results showed that the electrical flux was less than 1000 coulombs, indicating that the material has excellent resistance to chloride ion penetration.

[0121] 4.3 Microstructure Analysis

[0122] Scanning electron microscopy (SEM) observation

[0123] The hydration products were found to be more abundant and the pore structure more compact. The addition of slag powder promoted the hydration reaction and generated more CSH gel.

[0124] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.

Claims

1. A method for manufacturing new building materials using fly ash from municipal solid waste power generation, characterized in that, Includes the following steps: Step (1), Fly ash treatment: The fly ash generated from municipal solid waste incineration power generation is subjected to heavy metal stabilization treatment to reduce the leaching toxicity of heavy metals. Step (2), Preparation or selection of photocatalyst: Prepare or select materials with photocatalytic properties; Step (3), Preparation of mixture: Mix the stabilized fly ash, cementitious material, photocatalyst, aggregate and water to form a mixture with good workability; Step (4), molding and curing: Pour the mixture into the mold, vibrate and compact it to form building material products; cure the molded products until they meet the specified performance requirements.

2. The method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (1), the heavy metal stabilization treatment includes: mixing fly ash with diammonium hydrogen phosphate and ferrous sulfate heptahydrate, wherein the mass ratio of diammonium hydrogen phosphate to fly ash is m1:m FA =1:10, the mass ratio of ferrous sulfate heptahydrate to fly ash is m2:m FA =1:10; During the stirring process, add Δ per minute m =0.1m FA Calcium hydroxide was gradually added at a constant rate until the pH of the solution reached 10 ± 0.5; heavy metal ions Pb 2+ Cd 2+ Cr 3+ It reacts with phosphate and hydroxide ions to form insoluble phosphates and hydroxides. The reaction equation is as follows: M n+ +nOH - →M(OH) n ↓ Among them, M n+ These are heavy metal ions.

3. The method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (2), the photocatalyst is nitrogen-doped nano-titanium dioxide, and its preparation method includes: using tetrabutyl titanate as a precursor, dissolving it in anhydrous ethanol at a volume ratio of... Precursor solution A is formed; deionized water and glacial acetic acid are mixed at a volume ratio of... Solution B was formed, and the pH was adjusted to 3-4. Under ice bath conditions, solution A was slowly added to solution B at a dropping rate of u = 1 mL / min, and stirred for 2 hours to obtain a homogeneous sol. Urea was added to the sol at a molar ratio of n(CO(NH2)2):n(Ti(OC4H9)4) = 1:

1. After drying the gel, it was calcined at 500℃ under a nitrogen atmosphere at a heating rate of 5℃ / min for 3 hours, with a nitrogen flow rate of Q = 200 mL / min, to obtain nitrogen-doped nano-TiO2.

4. The method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (2), the nitrogen doping mechanism is as follows: urea decomposes at high temperature to produce ammonia (NH3). Nitrogen atoms in the ammonia gas replace oxygen atoms in the TiO2 lattice, forming TiO2. 2-x N x The reduction in band gap energy is due to the formula Description, in which ΔE represents the band gap energy of pure TiO2, while ΔE represents the reduction in band gap energy caused by doping, which enhances the response to visible light.

5. A method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (3), the mixing ratio of the mixture is as follows: stabilized fly ash: 30% of the total mass of cementitious materials; cement: 65%; nitrogen-doped nano-TiO2: 5%; Water-cement ratio = 0.35; water-reducing agent is added, accounting for 1% of the total mass of cementitious materials.

6. A method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (3), to prevent the agglomeration of nano-TiO2, nitrogen-doped nano-TiO2 is dispersed in the water-reducing agent solution by ultrasonic dispersion method. The ultrasonic frequency is f = 20kHz and the time is 30 minutes to form a stable nano suspension. The nano suspension is added to the mixer along with other raw materials. The stirring speed is 500rpm and the stirring time is 10 minutes to ensure the uniformity of the mixture.

7. A method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (4), the molding method is vacuum vibration molding: the mold is placed in a vacuum environment with a vacuum degree of P = -0.08MPa; the mold is vibrated at a vibration frequency of 50Hz for 2 minutes to improve the density and surface quality of the specimen.

8. A method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (4), during the curing process, steam curing is carried out after the initial curing: heating stage: heating up to 80℃ at a heating rate of 10℃ / h; constant temperature stage: keeping at 80℃ for 8 hours; cooling stage: cooling down to room temperature at a cooling rate of 10℃ / h; steam curing accelerates the hydration reaction of cement and fly ash and improves the early strength of the material.

9. A method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (4), the novel building material obtained has photocatalytic properties, and the testing method includes: immersing a 50mm×50mm×10mm specimen in a methylene blue solution with an initial concentration of C0=10mg / L and V=200mg / L; irradiating it with a 300W xenon lamp with a light intensity of I=100mW / cm². 2 The distance between the samples is 10 cm; samples are taken every 30 minutes, and the absorbance A of the solution is measured. t Calculate the degradation rate η; Where A0 is the initial absorbance; Within 3 hours, the degradation rate η is not less than 80%.

10. A method for manufacturing new building materials using fly ash from municipal solid waste power generation according to claim 1, characterized in that, In step (4), the mechanical property testing of the obtained new building material includes: testing the compressive strength of the cubic specimen using a pressure testing machine; the loading speed is v = 0.5 MPa / s; the compressive strength f c The calculation formula is: Where F is the failure load, A is the compression area (100mm×100mm); and the compressive strength at 28 days is f. c Not less than 50MPa.